THE UTILIZATION OF THE QUIZIZZ APPLICATION TO ENGLISH SUBJECT AT SMKN 14, JAKARTA PUSAT - Aryani, Rita; Hasan, Farah Soraya Djamal; Siahaan, Leroy Holman (English Review: Journal of English Education, 2022)
The era of disruption is hitting various fields, including education. This was accelerated by the emergence of a global pandemic that forced all societies to adapt to new habits, including the distance learning process. Innovations and creations are conducted to find the best alternative in the new standard era. Assessment is one thing that is essential to the educational process. Various ways and methods have been developed for conducting learning assessments. One of the web-based applications that can be used is Quizizz. This study aims to see and analyze the application of Quizizz to English subjects as an alternative to distance learning assessment. The data were collected by using a questionnaire, interview, observation, and document review. The participants of this study were the teachers of English, the vice-principal of facility and infrastructure, and the students. The findings of this study showed that the teachers of English at vocational high schools at SMKN 14 used hardware such as a projector, laptop, speaker, headset, and smartphone, while software such as the internet, dictionary application, e-book, Microsoft office, and browsing application. The teachers used discovery learning to utilize ICT in the syntax of the learning model. The background of the research was at SMKN 14 Jakarta. This study uses a qualitative approach with descriptive methods. Data analysis was performed using the triangulation technique. The results showed increased students' enthusiasm for using Quizizz as an alternative assessment of English subjects at school.